Prosedur Kedokteran Nuklir pada Anak - Erwin Affandi Soeriadi; Andrean Utomo (Jurnal Health Sains, 2021)
Childrens are different from adults in terms of organ maturity and the prevalence of diseases that often occur. Because of that, there are need for special skills in diagnosing diseases in children. Nuclear medicine diagnostic imaging is one of the modalities for diagnosing diseases in children. It takes special skills and techniques to perform nuclear medicine procedures in children. The cooperation of the child, the dose of radiopharmaceutical, and the dose of CT given are several important factors to support the examination. The purpose of this literature review is to discuss the preparation needed to carry out nuclear medicine examinations on children and the things that need to be considered in performing imaging on children. The type of literature review used is the narrative review method. Based on the criteria of inclusion and exclusion we get 17 articles related to the procedure and preparation of nuclear medicine actions in children